A framework for real‐time emissions trading in large‐scale vehicle fleets. Issue 3 (1st April 2015) - Häusler, Florian; Faizrahnemoon, Mahsa; Crisostomi, Emanuele; Schlote, Arieh; Radusch, Ilja; Shorten, Robert
Abstract : In this study a framework for the real‐time trading of budgeted emission rights between a fleet of participating vehicles is presented. The trading problem is formulated as a utility maximisation or as a utility fairness problem, which can be solved in real time either in a centralised or in a distributed manner. In both cases, the authors illustrate the basic issues that arise when such a framework is realised in practice, and they show the efficacy of the approaches by providing several simulation examples and a realistic case study.